Characteristics and Outcomes of Patients With Aortic Stenosis and Chronic Kidney Disease. Issue 3 (5th February 2019) - Patel, Krishna K.; Shah, Shailee Y.; Arrigain, Susana; Jolly, Stacey; Schold, Jesse D.; Navaneethan, Sankar D.; Griffin, Brian P.; Nally, Joseph V.; Desai, Milind Y.
Abstract : Background: We sought to study longer term survival in patients with aortic stenosis (AS) and nondialysis chronic kidney disease (CKD). Methods and Results: We studied 839 patients (aged 78±9 years and 51% male) with CKD and AS on echocardiogram from 2005 to 2012. Longer term all‐cause and cardiovascular mortality was compared with a CKD group without AS, propensity matched for age, sex, race, left ventricular ejection fraction and CKD stage. Cox models were used to evaluate all‐cause mortality and competing‐risks regression models censored at time of aortic valve replacement to evaluate cardiac mortality in patients with AS and CKD. Overall, 511 (61%), 252 (30%), and 76 (9%) patients had CKD stages 3a, 3b, and 4, respectively; 93% had hypertension, 28% had diabetes mellitus, and 37% had coronary artery disease. In total, 185 (22%) had mild AS, 355 (42%) had moderate AS, and 299 (36%) had severe AS (66 symptomatic). Patients with CKD and AS had higher cardiac and all‐cause mortality compared with controls with CKD and no AS ( P <0.001). Among patients with AS and CKD, there were 156 (19%) aortic valve replacements and 454 (54%) deaths (203 cardiac deaths) at 4.0±2.3 years of follow‐up. Lower estimated glomerular filtration rate (hazard ratio per 10 mL/min per 1.73 m 2 : 1.18; 95% CI, 1.08–1.29) was associated with increased risk of all‐cause mortality but not cardiac mortality (hazard ratio: 1.12; 95% CI, 0.97–1.30; P =0.13). Of patients undergoing aortic valve replacement, 61% had improvement in estimated glomerular filtration rate within 1 year (median percentage change=+2.8% per month). Conclusions: Among patients with nondialysis CKD, AS is associated with significantly higher cardiac and all‐cause mortality; lower estimated glomerular filtration rate is associated with increased mortality, and aortic valve replacement was associated with improved survival.